Effect of anxiety on students’ academic performance at secondary school level - Mahmood Khan Kakar; Sardar Fatima; Muhammad Shafi Malik (Review Journal of Social Psychology & Social Works, 2024)
Anxiety has numerous hindering factors that distract students from achieving satisfactory results in their examinations. The purpose of this study was to explore factors anxiety and their effects on students' academic performance at the secondary school level. For this purpose, three research objectives were made. The quantitative research design was used for this study and a convenient sampling technique was used to select the sample of 200 public secondary school teachers from Killa Saif Ullah and Muslim Bagh. The questionnaire comprised 36 close-ended statements developed on 5 5-point Likert-type scale. The reliability of the questionnaire was found at 0.81. The data were analyzed by using analysis and descriptive statistical techniques. The data were analyzed using descriptive and inferential statistics and an independent t-test was used through SPSS to find out the difference between genders' views. The findings of the study indicate that factors of anxiety (academic pressure, exams and assessments, parental expectations, competition, absent-mindedness, learning difficulties, and teacher-student relationships) exist and have a great effect on the academic performance of students. However, the study suggested a few strategies through which students can overcome their anxiety. The study recommended that students should keep themselves busy in productive activities, they should think positively about things and keep themselves focused.